1985
DOI: 10.1111/j.1469-8137.1985.tb03678.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOSYNTHESIS AND CARBOHYDRATE METABOLISM IN DETACHED LEAVES OF LOLIUM TEMULENTUM L.

Abstract: Summary Mature leaves of Lolium temulentum L. remained photosynthetically competent for some days following excision. During this time, amounts of soluble carbohydrate rose markedly and there was substantial accumulation of sucrosyl‐fructans. Cell‐free extracts of excised leaves showed enhanced ability to synthesize oligofructosides from sucrose in vitro. Excised leaves were capable of the synthesis of fructans from exogenous sucrose applied in the dark. Exposure of leaves to 14CO2 immediately following excisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 19 publications
6
53
0
Order By: Relevance
“…3). This is in agreement with previous research that has reported a correlation between SST activity and the level of sucrose in the tissue (5,6,8,12,13,15). However, it remains unclear whether the product of photosynthesis that actually induces SST activity is sucrose and not one of its metabolites.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…3). This is in agreement with previous research that has reported a correlation between SST activity and the level of sucrose in the tissue (5,6,8,12,13,15). However, it remains unclear whether the product of photosynthesis that actually induces SST activity is sucrose and not one of its metabolites.…”
Section: Discussionsupporting
confidence: 82%
“…SST emerged as a key regulatory enzyme because SST activity and the rate of fructan synthesis were closely correlated under various conditions (1 1-13), and because SST activity increased rapidly upon feeding of sugars (14) or treatments that cause accumulation of photosynthate, such as illumination of excised leaves ( 13) or cold treatments (8,12), and decreased equally rapidly upon treatments lowering the photosynthate level (13). It has been suggested that a threshold level ofsucrose in the tissue is the key for induction of SST and fructan biosynthesis (5,6,13,15).…”
Section: Introductionmentioning
confidence: 99%
“…One can be defined as specific 1-SST, because it forms practically only I-kestose and Glc from SUC. This enzyme is in a11 likelihood the same as the one previously characterized from barley protoplasts (Wagner and Wiemken, 1987), and it probably corresponds to the SST activities found in Lolium (Housley and Pollock, 1985;Cairns and Pollock, 1988) and in Agropyron (Chatterton et al, 1988). The other is a 6-SST that produces 6-kestose as the only trisaccharide but has some invertase activity.…”
Section: Enzymology Of Fructan Synthesismentioning
confidence: 61%
“…A decrease in the activity of this enzyme may be necessary if low temperature leads to increased storage of sucrose in the vacuole which would obviate osmotic problems imposed by high concentrations of cytoplasmic sucrose. The accumulation of sucrose in the vacuole could also serve to trigger fructan synthesis, even though the subsequent synthesis of fructan in the vacuole is predominantly from sucrose in the cytoplasm (Edelman & Jefford, 1968;Housley & Pollock, 1985). Although Al in the leaves is unlikely to be directly involved in the synthesis of the fructan precursor (Edelman & Jefford, 1968;Wagner, Keller & Wiemken, 1983), its role in the control of fructan synthesis on degradation has not been fully investigated.…”
Section: Discussionmentioning
confidence: 99%